COMMUNITY STRUCTURE OF SEAWEED AT COASTAL AREA OF HARUKU ISLAND, CENTRAL MOLLUCAS PROVINCE - Saleh Papalia (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The study of seaweed biodiversity was conducted in Ory, Pelaw, Kailolo, and Waimital coatal waters of Haruku island in 2011.  The purposes or this study were to determine the density and biodiversity of makroalgae in the coastal waters of the Haruku island. Data collection were conducted in June-September 2011 with square transect line method. The results showed that in the coastal area of Kailolo exhibited the highest value in density and biodiversity of macroalgae in the study regions with 47 species from 31 genera consisting  of 21 species of red algae, 14 species of green algae and 13 species of brown algae. Gracilaria, Acanthophora, Sargassum, Turbinaria, Caulerpa, and Halimeda were the most dominance in the region. The highest biomass of macroalga found in the Kailolo coastal waters was due to its relatively good habitat contidion consisting of dead coral rubble, sand, coral live with seagrass vegetation dominated by Thalasia hemprizii and Halodule uninervis. Meanwhile, habitat condition at the other locations had suffered a severe damage and dominated by dead coral. Environmental conditions in the study region  were within the limits of decent support for the growth of macro algae. Keywords: Macroalgae, diversity, biodiversity, substrat, Haruku island